Early childhood care and education trainees’ perspectives of their career path - Roznim Mohamad Rasli; Nor Azah Abdul Aziz; Erni Marlina Saari; Mazlina Che Mustafa; Sopia Md Yassin (International Journal of Evaluation and Research in Education (IJERE), 2021)
Education, either formal or informal, plays an important role to help the masses. As such, educators, especially trainees, are entrusted to teach young generations all important elements, principles, or concepts in a wide range of disciplines. Surely, such an undertaking, especially for early childhood care and education, requires quality teachers. In this regard, existing early childhood care and education modules or curricula should be periodically reviewed and revamped (if necessary) to help produce competent teachers who are excellent in all aspects encompassing content, pedagogical, and technological knowledge. This paper discusses the professional growth and development of trainees in early childhood care and education (ECCE) in terms of short- and long-term goals, missions, and career path-planning. The paper also elaborates on the relevant training workshops, courses, modules, and curricula that can be implemented to help improve their practical skills. The discussion also highlights the importance of incentives, such as attractive salaries, bonuses, acknowledgments, and awards, from employers that can not only motivate trainees but also advance their professional growth and development. Certainty, strong development knowledge, practical skills, and experiences can help such trainees to be become highly competent, which can significantly contribute to nation-building efforts in Malaysia.